Comparison of Quality of Life in Chronic Liver Disease Patients Based on Indonesian Version of SF-36 Questionnaire - Mustika, Syifa; Nuri, Sofia; Jauza, Nadia Alfiani; F, Sri Lestari; Nugroho, Rama Tiar; Kalal, Chetan Ramesh (The Indonesian Society for Digestive Endoscopy, 2025)
Background: Liver cirrhosis is a chronic progressive disease associated with substantial morbidity and mortality. Although clinical management often emphasizes physical outcomes, assessment of health-related quality of life (HRQoL) provides a more comprehensive evaluation of patient well-being. A validated multidimensional instrument for HRQoL assessment is SF-36 (36-Item Short Form Health Survey). Therefore, this study aims to compare HRQoL among patients with chronic hepatitis, liver cirrhosis, and hepatocellular carcinoma (HCC) using Indonesian version of SF-36. There are limited data from Indonesia comparing HRQoL across different stages of chronic liver disease, particularly including patients with chronic hepatitis.Methods: A cross-sectional study was conducted at Gastroenterohepatology Clinic of Saiful Anwar General Hospital, Malang, using 273 patients including 156 with chronic hepatitis, 88 with liver cirrhosis, and 29 with HCC. HRQoL was assessed using SF-36 questionnaire, which evaluated eight domains. Data were analyzed through Kruskal–Wallis test followed by Mann–Whitney post hoc analysis.Results: The results showed that HRQoL differed significantly across all SF-36 domains among the three groups (p 0.001), with the lowest scores observed in patients with HCC. Post hoc analysis showed a progressive decline in quality of life with increasing disease severity. However, no significant difference was found between cirrhosis and HCC groups in role limitations due to emotional problems (p 0.05).Conclusion: Advanced stages of chronic liver disease are associated with poorer HRQoL. Emotional role limitations appear less dependent on disease severity, signifying the need for psychological support across all stages.